-6d > 42
d < 42 / (-6)
d < -7
Answer:
7x - 42
Step-by-step explanation:
That's OK, but you have not said which variable you want to solve it for.
<u>To solve for 'x':</u>
<span>c + ax = dx
Subtract c from each side: ax = dx - c
Subtract dx from each side: ax - dx = -c
Factor the left side: x (a - d) = -c
Divide each side by (a - d) : x = -c / (a - d) or <u>x = c / (d - a)</u> .
</span><span><u>To solve for 'c': </u>
</span><span> c + ax = dx
Subtract ax from each side and factor: <u>c = x (d - a) </u>
</span><u>To solve for 'd': </u>
<span>c + ax = dx
Divide each side by 'x': d = c/x + a .
<u>To solve for 'a':</u>
</span><span><span> c + ax = dx</span>
Subtract 'c' from each side: ax = dx - c
Divide each side by 'x': <u>a = d - c/x </u>.
.</span>
Every point on the line 3/7x -1 is a solution
Unless there is another line provided...